Development of an automated cycle ergometer - Webster, J. M.; West, A.; Conway, P.; Cain, M. (Procedia Engineering, 2011)
Currently a substantial amount of cycling research and training is conducted in sports science laboratories utilising cycle ergometers and/or turbo trainers. These devices have been widely used within cycling research, however, they have been found to be difficult to set-up and adjust, particularly whilst in use as well as to replicate a force profile similar to that experienced when competing. This study details the development of a novel cycle ergometer that incorporates automatic bike set-up and adjustment. The ergometer was designed in accordance with a design specification developed through the use of needs analysis of elite cyclists and performance scientists. The user analysis identified a need for increased adjustability (seat height (SH), seat set back (SS), handlebar drop (HD) and handlebar reach (HBR)) and positioning accuracy, whilst maximising the stability and stiffness of the frame when conducting maximal effort trials particularly at the bottom bracket. The novel ergometer incorporates two lifting columns to provide HD adjustment from 411 mm to 868 mm and SH adjustment from 568 mm to 928 mm. The two lifting columns were mounted on two linear rails to provide horizontal adjustment of the handlebars relative to the seat, and seat relative to the bottom bracket. The motors on both the lifting columns and linear rails were fitted with HTL encoders, increasing the positioning accuracy to + /- 0.1 mm. An anti-coast brake was also fitted to prevent the lifting columns or linear rails from slipping whilst in use. When comparing existing set up time, adjusting from the largest to smallest set-up, current ergometers can take up to 30 minutes, whereas the new ergometer takes 8 seconds. To minimise twisting of the frame during maximal effort cycling, the bottom bracket has been mounted on a 65 mm x 65 mm square column. Finite element analysis of the structure identified that it would remain stable whilst subjected to up to 800Nm of torque. In conclusion the development of the novel ergometer allows for greater adjustability, speed of set-up and maximise frame stability during use.